Which factors are associated with the use of systemic antihistamines in patients with chronic hand eczema? Results from the CARPE registry - Apfelbacher, Christian; Weiss, M.; Molin, S.; Bauer, A.; Mahler, Vera; Schmitt, J.; Elsner, P.; Diepgen, T. L.; Weisshaar, E. (Journal of the European Academy of Dermatology and Venereology, 2016)
Antihistamines (AH) are often used to treat chronic skin diseases related to allergy and/or pruritus. Data on the use of AH in patients with chronic hand eczema (CHE) is scarce.The objective of this study was to investigate prevalence and determinants of AH use in patients with CHE.Data were drawn from the German CARPE registry. The relationship of clinical, demographic and treatment-related variables with AH use in the past 12 months was analysed by means of logistic regression. Odds ratios (OR) with corresponding 95% confidence intervals (CIs) were computed.A total of 1255 patients with CHE were eligible for analysis (54.1% female; mean age: 47.1 years, standard deviation (SD) 13.6 years). Mean subjective disease severity was 5.0 (SD 2.5). 25% of the sample reported to have used AH in the past 12 months. Significant positive associations with AH use were identified for moderate (OR = 3.05, 95% CI 1.81-5.15) or severe (OR = 4.27, 95% CI 2.40-7.59) pruritus, a history of systemic treatment (e.g. alitretinoin) (OR = 2.85, 95% CI: 2.06-3.96), UV phototherapy (OR = 1.78, 95% CI 1.28-2.46), flexural eczema (OR = 1.89, 95% CI 1.32-2.71), allergic rhinitis/conjunctivitis (OR = 2.41, 95% CI 1.71-3.39) and female gender (OR = 1.58, 95% CI 1.16-2.14) in multivariate analyses (N = 1184). Significant inverse associations were found for an eczema localization besides the hands (OR = 0.66, 95% CI 0.46-0.94) and for patients being recruited in hospital (vs. dermatological practice; OR = 0.47, 95% CI 0.33-0.67).This study suggests that AH use is frequent in patients with CHE and mainly related to female gender, disease severity, pruritus, comorbid atopic disease and treatment centre.
EVALuna2:19546